TOP as ligand and solvent to synthesize silver telluride nanosheets. (November 2015) - Chen, Shutang; Lee, Soonil
Graphical abstract: Highlights: Silver telluride nanosheets were prepared through one-pot synthetic strategy. TOP as both ligand and solvent favors silver telluride nanosheets growth. The I – V curve of an Ag2 Te-nanosheet film indicates that as-prepared Ag2 Te nanosheets have good electric conductivity. Abstract: Ag2 Te nanosheets are synthesized by a simple one-pot route using trioctylphosphine (TOP) as both solvent and stabilizer. Various controlling parameters were examined, such as molar ratios of AgNO3 to tellurium powder, reaction temperature and time, and precursor concentration. The morphology and composition of the products were characterized by X-ray diffraction, field-emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, and transmission electron microscopy. On the basis of a series of synthesis and characterizations, the formation mechanism of the Ag2 Te nanosheets are discussed. The I – V curve of an Ag2 Te-nan osheet film indicates that as-prepared Ag2 Te nanosheets have good electric conductivity.